Management of home care by family caregivers to elderly after hospital discharge - Rosangela Aparecida Elerati Silva; Camila do Nascimento Silva; Patrícia Pinto Braga; Denise Barbosa de Castro Friedrich; Ricardo Bezerra Cavalcante; Edna Aparecida Barbosa de Castro (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: To understand the management of home care by family caregivers of dependent elderly people after hospital discharge. Methods: Qualitative research guided by hermeneutics-dialectic, anchored in the theory of communicative action. Data collection took place using a semi-structured interview with 11 participants. Results: Two categories were constructed: Management of the many types of care by the caregiver and the relationship between family caregiver and health care network. Care and management actions carried out routinely cause major changes in the family caregiver's life. He/she does not recognize planning, home care periodicity or support in required procedures. Final Considerations: The management of home care for dependent elderly people after hospital discharge is complex, involving physical and emotional overloads, as well as difficulties in getting support from health services. The planning shared between the health team and the family since the discharge is required, and the better visibility of the role of primary care when the patient is assisted by a home care service.